Eleições presidenciais brasileiras e a volatilidade do IBOVESPA: relações com variáveis conjunturais e risco político - Henrique Nogueira Santana (2018)
The current political and economic instability of Brazil leads to think over its process of redemocratization and economic stabilization. This scenario brings to light the participation of events related to Political Risk in this stability disturbance. Elections are events related to risk and generate a reactionary behavior of financial markets, which raises the need to study the relationship between stock market assets and conjunctural economic indicators in periods of presidential elections. In this sense, this paper aims to investigate how the Ibovespa behaves before changes in economic conjuncture variables in periods close to presidential elections and impeachment processes. From a quantitative and descriptive survey, the return and volatility of Ibovespa in dollars were modeled against the following explanatory variables: logarithmic return of the MSCI world index; inflation rate; logarithmic variation of exchange rate; spread between Brazilian and American nominal interest rate (representing the risk premium for the foreign investor investing in Brazil); logarithmic variation of exchange rate risk (proxy for EMBI+ Brazil); logarithmic variation of the amount of paper money issued by the Central Bank; and dummies variables to control political events such as electoral processes, impeachment processes, chair alternation and party alternation. The modeling was an ARMAX-GARCH of orders (1,0) and (1,1), respectively. The basis for Ibovespa modeling through conjunctural economic variables was Chen, Roll and Ross (1986) and the basis for investigating volatility in the face of political events was Bialkowski, Gottschalk and Wisniewski (2008). The objective was to investigate whether presidential elections and impeachment processes are events that generate Political Risk capable to influence the returns and volatility of Ibovespa. The evidences points to the fact that elections and impeachment processes are political events that generate uncertainties, attributed to Political Risk, capable to reduce the Ibovespa returns and increase the volatility of returns. The alternation of party in the presidency also causes an increase of the volatility, but the chair alternation generates reduction of the volatility, both with no influence on returns of Ibovespa. It was verified that there is an inversion in the direction of the influence that the variables exert on the Ibovespa, so that the variables that cause positive effect in the average, cause negative effect on the variance and vice-versa. Finally, based on Bialkowski, Gottschalk and Wisniewski (2008), a dynamic Volatility Ratio vector was elaborate what allowed to verify the cyclical behavior of the Ibovespa’s returns volatility and their elevations when under influence of Political Risk. The Volatility Ratio also enabled graphically to verify the increase in volatility due to international crises.